Tanycytes of the hypothalamic median eminence form a diet-responsive neurogenic niche. (2012)
ABSTRACT:Adult hypothalamic neurogenesis has been recently reported, but the cell of origin and function of these newborn neurons are unknown. We utilize genetic fate mapping to show that median eminence tanycytes generate newborn neurons; blocking this neurogenesis alters weight and metabolic activity in adult mice. These findings describe a previously unreported neurogenic niche within the mammalian hypothalamus with important implications for metabolism.